Le Fahs d’Alger : une alternative pour la requalification du tourisme littoral ? - Ouassila Menouer; Mohamed Sahah Zerouala; Abdelkarim Dahmen (Études Caribéennes)
With its opening on the world market, the city of Algiers, or El-Djezaïr, (capital of Algeria) has become an attractive destination for business tourism. Although, its coast, rich in beaches and seaside resorts, often undergoes a massive tourism that endangers its environment identity. Hence, it would be of first interest to set-up a touristic development strategy aiming the littoral safeguard. The main scope of this paper is the littoral tourism requalification in Algiers by reinterpreting the leisure and recreation facilities that existed there before 1830. Moreover, it focus on the valuation of its territorial heritage: fountains, summer residences, and mostly the natural paths that used to connect the city port to the hinterland since the earliest times.Indeed, before 1830, El-Djezaïr had its "Fahs”, a territory famous by its "djenanes": a kind of summer residences within fabulous gardens facing the sea. Often seemed like deserted museums, the "djenanes" could constitute a key opportunity coastal tourism requalification. One of the alternatives would be their reconversion into touristic structures for scientific, business, leisure and recreational tourism. The paper presents the case of “La Villa du Traité”, a commemorative place related to the capitulation of the city of Algiers in 1830. The place is proposed to become a center of ethics where national and international scientific events in Medicine could be held.